Impact of Remote Monitoring on Long-Term Prognosis in Heart Failure Patients in a Real-World Cohort: Results From All-Comers COMMIT-HF Trial. - KUREK, ANNA; TAJSTRA, MATEUSZ; GADULA‐GACEK, ELZBIETA; BUCHTA, PIOTR; SKRZYPEK, MICHAL; PYKA, LUKASZ; WASIAK, MICHAL; SWIETLINSKA, MALGORZATA; HAWRANEK, MICHAL; POLONSKI, LECH; GASIOR, MARIUSZ; KOSIUK, JEDRZEJ (Journal of Cardiovascular Electrophysiology, 2017)
Remote Monitoring in Real-World Cohort Background Randomized controlled trials demonstrate that remote monitoring (RM) of implantable cardioverter-defibrillators (ICDs) and cardiac resynchronization therapy devices (CRT-Ds) may improve quality of care and prognosis in heart failure (HF) patients. However, the impact of RM on long-term mortality in a real-world cohort is still not well examined. Methods and Results This study was designed as a matched cohort study based on the COMMIT-HF trial--a single-center, ongoing prospective observational registry (NCT02536443). Complete patient demographics, medical history, in-hospital results, hospitalizations, and mortality data were collected based on institutional registries and healthcare providers' records. Patients were divided into 2 groups based on RM presence and matched by means of propensity scores according to clinical characteristics. The primary endpoint of this study was the long-term all-cause mortality. Out of 1,429 consecutive patients, 822 patients with a first implantation of an ICD/CRT-D were included in the analysis. The final matched study population contained 574 patients in RM and in a control group. Although demographic and echocardiographic parameters as well as pharmacological treatments were similar in both groups, a significantly lower 1-year mortality was detected in the RM group (2.1% vs. 11.5%, P < 0.0001). This was also maintained during a 3-year follow-up (4.9% vs. 22.3%, P < 0.0001). Multivariate analysis showed that RM was associated with an improved prognosis (hazard ratio 0.187, 95% confidence interval 0.075-0.467, P = 0.0003). Conclusion RM of HF patients with ICDs/CRT-Ds significantly reduced long-term mortality in a real-world clinical condition.